0222 Night work and breast cancer risk among women in the public Danish health care sector - a short-term follow up of a large scale population. (23rd June 2014) - Tilma Vistisen, Helene; Helene Garde, Anne; Marie Hansen, Aase; Hansen, Johnni; Christiansen, Peer; Kolstad, Henrik
Abstract : Objectives: Experimental evidence suggest a short-term effect of light at night on breast cancer oncogenesis. We studied the short-term effect of night work on breast cancer occurence. Method: We established a large, national cohort of employees in the public health care sector with a high prevalence of night shift work and with detailed data regarding occupational title and date and hour for beginning and end of every work duty: The Danish Working Hour Database (DWHD). DWHD encompasses payroll data as of 2007 and is updated on an annual basis. For this analysis we defined night work as at least 3 h of work between midnight and 05:00. From national cancer registers we retrieved information about breast cancer diagnosis for all female workers and their relatives. Reproductive history, hormone medications, attendance in mammography screening, and vital status were obtained from other national health registries. Results: The 6-year follow up from 2007 to 2012 included 169.011 women of which 98.297 (58%) had ever worked nights during the follow up. A total of1.281 breast cancer cases occurred within the study population. 846 cases occurred among women never worked nights and 435 cases among women ever worked nights. Conclusions: Internal risk assessment of this dataset that includes alternative exposure metrics based on day-to-day night work exposure information will be presented.